Optimising the use of Barley straw in Tropical Ruminant Diets - Keno, Mulugeta (Jimma University, College of Agriculture and Veterinary Medicine, 2022)
This thesis provides a general overview of barley straw utilization and the means for its improvement in Ethiopian mixed crop-livestock farming systems. Most Ethiopian households store crop residues in exposed heaps which may lead to heavy loss in biomass and nutritive value due to feed spoilage. Hence, application of appropriate storage and management options to avoid wastage or spoilage of the straw is necessary. The high variation in grain and straw yield and quality among barley cultivars points to the possibility of improving yield and quality traits in the study area through selection. The cultivars that were chosen as the most promising from this PhD work were selected based only on their performance in one year. Including data from at least a second year would have made these conclusions more robust, but the large differences in performance between the growing locations demonstrates the necessity of considering environmental influences, such as geological and climatological conditions, to avoid missing the optimal cultivars for a specific General Discussion 123 condition. In addition, in vitro analysis does not cover all aspects of nutritive value for animals, meaning that, at least for crucial decision steps, animal studies will be needed to get an accurate ranking of barley cultivars. With the ongoing deterioration of farming land in barley-livestock farming systems, and the concomitant decrease in grain and straw production, methods are needed to further optimize the multi-purpose use of barley straw for food, feed, and soil mulch.